Persepsi Siswa Terhadap Materi Fisika KD Hakikat Fisika Di Kelas X IPA 1 Pasca Covid-19 - Muh. Fatkhul Ma’arij (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
The diagnostic test carried out at the beginning of the meeting, informs that the physics subject matter is difficult, complicated, many formulas, memorizing formulas has not guaranteed to be able to do physics problems correctly. The negative perception of most students shows that online physics learning in junior high schools due to the Covid-19 pandemic is a challenge for physics teachers, especially students have determined to enter the science department. Qualitative methods by conducting a simple pendulum experimental learning process determine the acceleration of gravity. The formative test results show that students like physics, the perception of physics material is mostly positive, although it does not necessarily make students easy to learn physics. In this study, the causes of learning difficulties were mostly due to the Covid-19 pandemic so that experimental activities that characterized physics learning did not run. with an emphasis on the benefits of learning physics and the application of physics in everyday life and focusing on the process of science (competence) caused some students to realize that physics is so close to daily life that perceptions of physics have increased, although the online learning process due to covid-19 in the past caused some students to express their pleasure in learning physics even though physics is difficult.